OPTIMIZATION MAP FOR EARTHQUAKE DISASTER EVACUATION INFRASTRUCTURE IN THE LEMBANG FAULT AREA BY CONSIDERING THE DANGER OF EARTHQUAKE IMPACTS (CASE STUDY OF LEMBANG SUBDISTRICT) - Mahardika, Fahmi
The Lembang Fault is one of the active faults in Indonesia, specifically in West Java Province, stretching approximately 29 km west-east in the north of the Bandung Basin. The location is next to dense residential areas and is a tourist attraction, namely Lembang. GPS data shows that there is a small shift of around 0.3 to 1.4 cm/year on the Lembang fault. It is also said that the Lembang fault could potentially produce shocks of magnitude 6.5 - 7. This certainly needs to be a focus in response efforts to earthquake disasters. The aim of this research is to create a disaster evacuation system in the form of an evacuation map, which consists of recommendations for the distribution of evacuation places and evacuation routes using a safe area approach to the dangers that can be caused by earthquakes and several other predetermined criteria. The method used in determining evacuation routes is network analysis using isochrone maps to determine the reachability of evacuation places from each point of origin, then a routing process is carried out using network analysis to find the shortest route based on the distance from the point of origin to the destination point. The results of the evacuation maps that have been created will be compared with existing results, as input or recommendations for better evacuation infrastructure results.